CCDC42 Localizes to Manchette, HTCA and Tail and Interacts With ODF1 and ODF2 in the Formation of the Male Germ Cell Cytoskeleton - Tapia Contreras, Constanza; Hoyer-Fender, Sigrid (Frontiers in Cell and Developmental Biology, 2019)
Terminal differentiation of male germ cells into functional spermatozoa requires shaping and condensation of the nucleus as well as the formation of sperm specific structures. A transient microtubular structure, the manchette, is mandatory for sperm head shaping and the development of the connecting piece and the sperm tail. The connecting piece or head-to-tail coupling apparatus (HTCA) mediates the tight linkage of sperm head and tail causing decapitation and infertility when faulty. Using mice as the experimental model, several proteins have already been identified affecting either the linkage complex or manchette or tail formation when missing. However, our current knowledge is far too rudimentary to even draft an interacting protein network. Depletion of the major outer dense fiber protein 1 (ODF1) mainly caused decapitation and male infertility but validated binding partners collaborating in the formation of sperm specific structures are largely unknown. Amongst all candidate proteins affecting the HTCA when missing, the structural protein CCDC42 attracted our attention. The coiled-coil domain containing 42 (CCDC42) is important for HTCA and sperm tail formation but is otherwise largely uncharacterized. We show here that CCDC42 is expressed in spermatids and localizes to the manchette, the connecting piece and the tail. Beyond that, we show that CCDC42 is not restricted to male germ cells but is also expressed in somatic cells in which it localizes to the centrosome. Although centrosomal and sperm tail location seems to be irrespective of ODF1 we asked whether both proteins may form an interacting network in the male germ cell. We additionally considered ODF2, a prevalent protein involved in the formation of spermatid-specific cytoskeletal structures, as a putative binding partner. Our data depict for the first time the subcellular location of CCDC42 in spermatids and deepen our knowledge about the composition of the spermatid/sperm specific structures. The presence of CCDC42 in the centrosome of somatic cells together with the obvious restricted male-specific phenotype when missing strongly argues for a compensatory function by other still unknown proteins most likely of the same family.